PERANCANGAN DAN PEMBUATAN TETARING DENGAN INOVASI MATERIAL DAN MEMPUNYAI NILAI ESTETIKA - Gunantara, N.; Sasmita, G.M.A.; Dwijendra, N.K.A.; Dewi, A.A.D.P.; Mataram, I.M. (Buletin Udayana Mengabdi; Vol 20 No 1 (2021): Buletin Udayana Mengabdi, 2021)
In carrying out the ceremony at the Sindetan Temple, Les Village, we always keeps his tetaring. The tetaring that is installed is usually made of materials, namely bamboo, slepan (coconut leaves), and rope. In making the tetaring, a lot of manners are needed and have expertise in making tetaring. In addition, the cost of making the tetars is quite expensive and takes a long time. After completing the piodalan, the tetaring is dismantled where the materials cannot be reused for the next piodalan ceremony. This is because these materials will spoil quickly. The solution to this problem is in the form of innovation in making tetaring from materials that are more durable and stronger. The materials to be used are iron and cloth. This iron is used as a substitute for bamboo and cloth is used as a substitute for slepan and rope. The Service Team has designed the tetaring that will be made so that it has aesthetic value to be seen. In addition, the tetaring will be made easy and comfortable to use and can be assembled and assembled. Tetaring can be dismantled, meaning that if it is to be used, it will be easy to install and vice versa when it is finished, it will be easy to dismantle. The tetaring design is then realized and has been supervised in the process. The tetaring that have been made are installed at Sindetan Temple and then handed over to the Sindetan Temple board. This will provide effectiveness and efficiency for the Pura Sindetan boarding house. So that the manners of Pura Sindetan don't bother anymore thinking about tetaring when there is a piodalan ceremony.